2021
DOI: 10.1161/strokeaha.121.035233
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal of Life-Sustaining Treatment Mediates Mortality in Patients With Intracerebral Hemorrhage With Impaired Consciousness

Abstract: Background and Purpose: Impaired level of consciousness (LOC) on presentation at hospital admission in patients with intracerebral hemorrhage (ICH) may affect outcomes and the decision to withhold or withdraw life-sustaining treatment (WOLST). Methods: Patients with ICH were included across 121 Florida hospitals participating in the Florida Stroke Registry from 2010 to 2019. We studied the effect of LOC on presentation on in-hospital mortality (primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…In addition to disease severity, we found that older age, level of consciousness, state region, white race, insurance status, ambulation status at baseline, and stroke center type are important factors contributing to the decision of WLST. Our results are consistent with prior publications regarding older age, baseline functional status, level of consciousness and race (10–13). The higher rates of WLST in comprehensive stroke centers may reflect a sicker population (with more comorbidities, and more severe strokes) than those in other center types.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition to disease severity, we found that older age, level of consciousness, state region, white race, insurance status, ambulation status at baseline, and stroke center type are important factors contributing to the decision of WLST. Our results are consistent with prior publications regarding older age, baseline functional status, level of consciousness and race (10–13). The higher rates of WLST in comprehensive stroke centers may reflect a sicker population (with more comorbidities, and more severe strokes) than those in other center types.…”
Section: Discussionsupporting
confidence: 93%
“…Patient and family values and preference, self-fulfilling prophecy (driven by poor prognosis beliefs), and cognitive biases in prognosis shortly after injury may lead to the decision to withhold or withdraw of life-sustaining therapies (WLST) (6)(7)(8)(9). WLST is more commonly seen after ICH and SAH than AIS (9)(10)(11). Factors such as age, stroke severity, and impaired level of consciousness may influence WLST decisions (10)(11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of patients who died had low GCS scores at admission. Impaired level of consciousness has been associated with higher mortality, mediated through withdrawal of life sustaining treatment [ 20 ]. However, not all patients with DNAR decisions in our study received palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, such decisions can be enormously disruptive for both patients and their families. In cases where key stakeholders (i.e., patients if able vs. family) agree that further interventions would in fact be futile, treatment-limiting decisions (TLDs) may ultimately be implemented [ 5 ]. Clinicians not only shoulder the medical responsibility for implementing such TLDs, but often face additional time constraints in decision-making and providing support/guidance to patients/family members.…”
Section: Introductionmentioning
confidence: 99%